Pre-service English Teachers in the Teaching Internship Program (TIP) - Ghufron, M. Ali (Jurnal Pendidikan Indonesia, 2024)
The Teaching Internship Program is designed to prepare prospective teachers for the world of work, but participants still face many challenges. This study aims to analyze the challenges and opportunities pre-service English language education student teachers face during the Teaching Internship Program in secondary schools in Indonesia. The study used a qualitative approach with a case study method, and data was collected through semi-structured interviews and reflective journals. The analysis was carried out through an inductive process in three phases: open coding (identifying and categorizing themes), axial coding (exploring relationships between themes), and selective coding (highlighting relevant themes for further discussion). The findings showed that participants faced several challenges during the PPL, especially in classroom management, effective delivery of subject matter, and handling non-teaching tasks. The experiences of pre-service English language education teachers in the Teaching Internship Program (TIP) varied greatly, influenced by individual factors, institutions, and the school environment where they were interned. The implications of this study indicate the need to improve the quality of the Teaching Internship Program (TIP) to maximize participants' learning experience. The research results underline the importance of the role of mentors in providing practical guidance, so educational institutions and partner schools need to develop training programs for mentors to ensure they have adequate mentoring skills.